Consciousness and inward electromagnetic field interactions - MacIver, M. Bruce (Frontiers in Human Neuroscience, 2022)
Electromagnetic field (EMF) theories of mind/brain integration have been proposed to explain brain function for over seventy years.(Köhler and Held, 1949) Interest in this theory continues to this day because it explains mind-brain integration and it offers a simple solution to the ‘binding problem’ of our unified conscious experience. EMFs are easily measured and many corelates have been noted for field activity; associated with loss and recovery of consciousness, sensory perceptions and behavior.(Dyba et al., 2021; Keppler, 2021; Young, Hunt and Ericson, 2021; Hales and Ericson, 2022; Kitchener and Hales, 2022; Young, Robbins and Shelat, 2022) Unfortunately, the theory was challenged early on by experiments that were thought to have ruled out a role of EMFs in brain activity.(Lashley, Chow and Semmes, 1951; Sperry, Miner and Myers, 1955), and the field of neuroscience has since marginalized EMF theories. Here I explain why early evidence against EMFs contributing to consciousness was misinterpreted and offer an alternative view to help direct future research.